From Medical Data to Health Knowledge - Martin, J. M.; Benamghar, L.; Junod, B.; Marrel, P. (Methods of Information in Medicine, 1987)
The problems of assisting in the medical decision-making process are attracting more and more attention.Actually a certain number of computer systems have considerably improved the availability of medical data. However, we encounter some difficulties when extending these systems. In order to surmount these problems, it is necessary to proceed further in the analysis and comprehension of medical information and processes.To accomplish this goal, it is necessary to have a better understanding of the way in which a group of medical data is derived from one piece of medical knowledge and also how a chunk of medical knowledge is related to its corresponding medical data.This article is a beginning in the study of the transition from medical data to health knowledge, and this transition represents only part of the global entity, the nature, the representation, and use of medical information.
Keywords: Medical Data; Health Knowledge; Decision-Making